Use and Awareness of Open Access Resources among Researchers: a Case Study of Raman Research Institute - Nagaraj, M. N.; Bhandi, M. K. (Journal of Information and Knowledge, 2016)
This paper presents the key findings of a survey about use, awareness and utilization of open access resources and selected Web 2.0 tools among physics researchers. Open Access (OA) resources are classified into two categories: primary sources of information with full text access including databases and Web 2.0 applications like ResearchGate, Wikipedia and personal blogs. The population chosen for this study were physics researchers of Raman Research Institute (RRI), Bangalore, India. A structured questionnaire was distributed to 120 physics researchers;. 102 responses were obtained. The analysis revealed that physics researchers are aware and using subject based repositories like arXiv. It is found that around fifty-one per cent of users are satisfied with available OA resources.